14th International Symposium on Advanced Materials. (August 2016) - Qaisar, Sara; Khan, A. Nusair; Mukhtar, Ejaz Ahmed
Abstract : Advanced Materials XIV is a compilation of peer reviewed papers presented at the 14 th International Symposium on Advanced Materials (ISAM 2015) held from October 12- 16 th 2015 at the National Centre for Physics, Islamabad, Pakistan. In the role of Secretary ISAM-2015, I feel honored that the symposium ended on a positive note. The challenges of the present day industry entail an indepth knowledge of the science behind the processes involving advanced materials. It is this need that ISAM, along with similar other forums, endeavors to address. The five day deliberations of ISAM 2015, consisted of 29 technical sessions and 2 poster sessions, inclusive of a poster competition on nanostructures which displayed 150 research papers depicting various aspects of nanomaterials. In all 307 papers were presented, inclusive of 61 contributory, invited and oral presentations. The symposium also hosted 3 parallel panel discussions led by renowned scientists and eminent researchers from foreign as well as local institutes. The ultimate aim of this proceeding is to archive various findings in the field of advanced materials. I hope that the technical data available in this publication proves its worth to scientists and researchers working in this area of science. I wish to acknowledge the Institute of Physics (IOP) Publishing UK, for accepting the research papers from ISAM-2015 for publication in the IOP Conference Series: Materials Science and Engineering. The proceeding will be available on the IOP website as an online open access document. I am profoundly thankful to the Symposium Chairman for his firm support and for the wisdom with which he guided the Organizing Committee of ISAM 2015 to make it a successful event. On the same note, I must sincerely acknowledge the truly commendable efforts of the organizing committee. My gratitude to all our distinguished participants, session chairs/co-chairs, and reviewers for their active role in the symposium. Last yet not the least, my thankfulness goes to all our sponsors for financing the event.